2009
DOI: 10.1021/jp9024816
|View full text |Cite
|
Sign up to set email alerts
|

Chemical State of Nitrogen and Visible Surface and Schottky Barrier Driven Photoactivities of N-Doped TiO2 Thin Films

Abstract: N-doped TiO 2 thin films have been prepared by plasma enhanced chemical vapor deposition and by physical vapor deposition by adding nitrogen or ammonia to the gas phase. Different sets of N-doped TiO 2 thin films have been obtained by changing the preparation conditions during the deposition. The samples have been characterized by X-ray diffraction, Raman, UV-vis spectroscopy, and X-ray photoemission spectroscopy (XPS). By changing the preparation conditions, different structures, microstructures, and degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 64 publications
5
60
0
3
Order By: Relevance
“…Previous studies in literature have attributed different N 1s peaks in N-doped TiO 2 to nitride and oxinitride species of the type: Ti-N ͑396.3 eV͒, Ti-ON ͑399.3 eV͒, and Ti-NO ͑400.7 eV͒. 8 According to these previous assignments, the spectra in Fig. 3͑b͒ support the formation of a high concentration of Ti-N species in the implanted samples.…”
Section: B Structural and Chemical Characterization Of The Implantedsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies in literature have attributed different N 1s peaks in N-doped TiO 2 to nitride and oxinitride species of the type: Ti-N ͑396.3 eV͒, Ti-ON ͑399.3 eV͒, and Ti-NO ͑400.7 eV͒. 8 According to these previous assignments, the spectra in Fig. 3͑b͒ support the formation of a high concentration of Ti-N species in the implanted samples.…”
Section: B Structural and Chemical Characterization Of The Implantedsupporting
confidence: 66%
“…5 For these applications, it was found that the anatase crystalline phase is especially adequate to optimize many of the previous properties, and that its performance clearly improves when the film surface is nanostructured 6 and/or when it is doped with nitrogen to shift its spectral response from the ultraviolet toward the visible light spectrum. 7,8 The development of reliable techniques for surface nanostructuring of thin films is nowadays a key issue that has been approached by different physical and chemical methods. 9 In particular, considerable efforts have been devoted during the last years to the preparation of mesostructured 10 and one-dimensional TiO 2 structures ͑na-norods, nanowires, and nanotubes͒ 11,12 which have depicted unprecedented results as hydrogen sensors, self-cleaning surfaces under ultraviolet light exposure, or dye sensitized heterojunction solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of N 1s peaks in N-doped TiO 2 by XPS remains a controversial issue. The N 1s peak found at a binding energy (BE) of around 397 eV has been often assigned as substitutional N-doping, while N 1s peaks at BE4398 eV have been assigned to interstitial N-doping [30][31][32]. The binding energy of N 1s is highly dependent on the methods and conditions of preparation.…”
Section: Xps Analysismentioning
confidence: 99%
“…Doping of metal ions such as Cr, V, Fe, Pb, Cu has been explored [39][40][41], but it should be noted that improvement has not been observed in all cases. Non-metal doped TiO 2 (C-N-F doped TiO 2 ) thin films are also active under visible-light irradiation and can therefore act as self-cleaning surfaces [42][43][44]. It is generally observed that non-metal doping is more promising than metal doping to produce visible-light photocatalytic activity.…”
Section: Self-cleaning Action Of Metal Oxide With Metal and Non-metalmentioning
confidence: 99%